Geographical and Cartographic Characteristics of use of Alternative Energy Resources in Uzbekistan - Tolaev Bobur Bakhodir O’g’li (Zien Journals, 2022)
In this article, average daily and annual sunlight falling on the horizontal surface of the territory of the Republic of Uzbekistan was analyzed. In addition, the geographical distribution of the technical potential of wind alternative energy resources in Uzbekistan was analyzed and a digital map was created in the geodatabase. Methodology for creating alternative energy resources maps was developed using international experience and national level research. Geodetic survey of energy objects for the use of alternative energy resources is carried out, and methods of measuring are determined
Keywords: database, electronic map, alternative energy, topographic survey, GPS device, Credo CAD software and AutoCAD software